Pharmacokinetic study of gallocatechin-7-gallate from Pithecellobium clypearia Benth. in rats - Chao Li; Xiaowei Song; Junke Song; Xiaocong Pang; Zhe Wang; Ying Zhao; Wenwen Lian; Ailin Liu; Guanhua Du (Acta Pharmaceutica Sinica B, 2016)
The pharmacokinetic profile of gallocatechin-7-gallate (J10688) was studied in rats after intravenous administration. Male and female Sprague-Dawley (SD) rats received 1, 3, and 10 mg/kg (i.v.) of J10688 and plasma drug concentrations were determined by a high performance liquid chromatography-mass spectrometry (LC–MS) method. The pharmacokinetic software Data Analysis System (Version 3.0) was used to calculate the pharmacokinetic parameters. For different i.v. doses of J10688, the mean peak plasma concentration (C0) values ranged from 11.26 to 50.82 mg/L, and mean area under the concentration-time curve (AUC0–t) values ranged from 1.75 to 11.80 (mg·h/L). J10688 lacked dose-dependent pharmacokinetic properties within doses between 1 and 10 mg/kg, based on the power model. The method developed in this study was sensitive, precise, and stable. The pharmacokinetic properties of J10688 in SD rats were shown to have rapid distribution and clearance values. These pharmacokinetic results may contribute to an improved understanding of the pharmacological actions of J10688.